Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran PAI melalui Cooperative Learning Model Time Token - Salimah, Lili; Setiawati, Endang; Mu'awanah (LPTK IAIN Kediri, 2024)
This research started from the problem of low PAI learning activity among class IV students at SDN 3 Sidawangi, Cirebon Regency. The aim of this research is to describe the process of implementing the Cooperative Learning Time Token learning model in PAI learning and to describe the increase in student learning outcomes in learning after implementing the model. The type of research used is classroom action research which consists of 2 cycles, where each cycle applies the Kurt Lewin model of action research design in the form of planning, implementation, observation and reflection. Data collection was carried out by observation and written tests. The research results show that the Cooperative Learning Time Token model can improve PAI learning outcomes for class IV students at SDN 3 Sidawangi, Cirebon Regency. This is proven by the value of learning outcomes which experienced an increase in completeness from 33.33% in the pre-cycle stage, to 74.07% in Cycle 1, and 81.48% in cycle 2. This shows that the Cooperative Learning Time Token model is a model appropriate for improving student learning outcomes in PAI learning for class IV students at SDN 3 Sidawangi, Cirebon Regency.